First and recurrent ischaemic heart disease events continue to decline in New Zealand, 2005–2015. Issue 1 (29th June 2017) - Grey, Corina; Jackson, Rod; Wells, Susan; Wu, Billy; Poppe, Katrina; White, Harvey; Chan, Wing Cheuk; Kerr, Andrew J
Abstract : Objectives: To examine recent trends in first and recurrent ischaemic heart disease (IHD) deaths and hospitalisations. Methods: Using anonymous patient-linkage of routinely collected data, all New Zealanders aged 35–84 years who experienced an International Statistical Classification of Diseases and Related Health Problems I(CD)-coded IHD hospitalisation and/or IHD death between 1 January 2005 and 31 December 2015 were identified. A 10-year look-back period was used to differentiate those experiencing first from recurrent events. Age-standardised hospitalisation and mortality rates were calculated for each calendar year and trends compared by sex and age. Results: 160 109 people experienced at least one IHD event (259 678 hospitalisations and 35 548 deaths) over the 11-year study period, and there was a steady decline in numbers (from almost 24 000 in 2005 to just over 16 000 in 2015) and in age-standardised rates each year. With the exception of deaths in younger (35–64 years) women with prior IHD, there was a significant decline in IHD events in men and women of all ages, with and without a history of IHD. The decline in IHD mortality was greater for those experiencing a first rather than recurrent IHD event (3.8%–5.2% vs 0%–3.7% annually on average). In contrast, the decline in IHD hospitalisations was greater for those experiencing a recurrent compared with a first IHD event (5.6%–7.3% vs 3.2%–5.7% annually on average). Conclusions: The substantial decline in IHD hospitalisations and mortality observed in New Zealanders with and without prior IHD between 2005 and 2015 suggests that primary and secondary prevention efforts have been effective in reducing the occurrence of IHD events.